The Efficiency and Effectiveness of the Managerial Methodological System - Ion VERBONCU, Ph. D.; Ştefan-Florin CORCODEL (Revista de Management Comparat International, 2013)
The main objective of this manuscript is to present a perspective on two characteristics of the methodological component of the management system – its efficiency and its effectiveness. Multiple measures of these characteristics are presented within the paper. In addition to this, we have highlighted the most important ties between the instruments that compose this subsystem and the economical performances that can obtained through their promotion, establishment and usage within an organization. The analyzed instruments include major management systems (like management based on profit centres, management by objectives and others) and the most used methods: the diagnostic method, the dashboard method, the delegation method. All of these instruments have certain effects on the economic and financial situation of a firm, effects that are highlighted within this paper.